Cobalt nanoparticle / aza-carbon composite material and preparation method and application thereof
By uniformly dispersing Co2+ salt and nitrogen source in radish cells, a cobalt nanoparticles/aza carbon composite material was prepared, which solved the problem of easy agglomeration of cobalt nanoparticles and difficult to control particle size, and achieved efficient photocatalytic degradation effect.
Patent Information
- Application Number
- CN202510063526.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-25
AI Technical Summary
Pure carbon-based photocatalytic degradation materials have low catalytic degradation efficiency on organic matter. Ultrafine cobalt nanoparticles are prone to agglomeration and difficult to control their particle size, resulting in poor catalytic stability and efficiency.
Using radish as raw material, the soluble Co2+ salt and nitrogen source are uniformly dispersed into the radish cells by cell template method. After freeze-drying and calcining, a cobalt nanoparticles/aza carbon composite material is prepared to achieve high dispersion and controllable particle size of cobalt nanoparticles.
The specific surface area and active sites of cobalt nanoparticles are improved, and a photocatalyst is provided to efficiently degrade chloroquine phosphate and various organic pollutants in water, achieving continuous oxidative degradation effect.
Smart Images

Figure CN119869588A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of photocatalytic degradation materials, and in particular to a cobalt nanoparticle / nitrogen-carbon composite material and a preparation method and application thereof. Background Art
[0002] Chloroquine phosphate (CQ) is a traditional antiviral drug for malaria. Due to its extensive use in the treatment of coronavirus disease in recent years, chloroquine phosphate has become a new detectable pollutant in natural water bodies. In the field of wastewater treatment, photocatalytic degradation materials for organic pollutants are becoming more and more popular, but the application of most degradation materials is limited by their complex preparation process and high cost.
[0003] Carbon-based photocatalytic degradation materials have low preparation costs and broad application prospects. They are one of the preferred materials for photocatalytic degradation of organic pollution. However, pure carbon-based photocatalytic degradation materials are not efficient in catalytic degradation of organic matter. Ultrafine cobalt nanoparticles have become a catalyst of widespread concern due to their efficient atomic utilization and abundant active centers. However, ultrafine cobalt nanoparticles are easy to agglomerate and their particle size is difficult to control, resulting in poor catalytic stability and poor catalytic effect. Summary of the invention
[0004] The present invention provides a preparation method and application of a cobalt nanoparticle / nitrogen-carbon composite material using radish as a raw material, which effectively solves the technical problems that the pure carbon-based photocatalytic degradation efficiency is poor, and the cobalt nanoparticles are easy to agglomerate and the particle size is difficult to control, resulting in poor catalytic stability and catalytic efficiency. The present invention achieves high dispersibility and controllable particle size of cobalt nanoparticles, effectively increases the specific surface area and active sites of cobalt nanoparticles, and provides a photocatalyst for the efficient degradation of chloroquine phosphate and various organic pollutants in water.
[0005] The first object of the present invention is to provide a method for preparing a cobalt nanoparticle / nitrogen-carbon composite material, comprising the following steps:
[0006] Soak the shredded radish in a 35℃~45℃ water containing soluble Co 2+ Salt and nitrogen source solution, based on the cell template method, soluble Co 2+ The salt and nitrogen source are evenly dispersed into the radish cells, and after freeze drying and grinding, the precursor of the cobalt / nitrogen-carbon composite material is obtained;
[0007] The precursor of the cobalt / nitrogen-carbon composite material is heated to 400° C. to 450° C. under a protective atmosphere and calcined to obtain the Co 2+ The nitrogen source and shredded radish are converted into nitrogen-carbon to obtain a cobalt nanoparticle / nitrogen-carbon composite material.
[0008] As a preferred embodiment, in the cobalt nanoparticle / nitrogen-carbon composite material, the loading amount of cobalt nanoparticles is 3% to 5%, and the nitrogen atomic fraction is 1.9% to 2.2%.
[0009] As a preferred implementation, the soaking time is 10 to 12 hours.
[0010] As a preferred embodiment, the calcination time is 2 hours.
[0011] As a preferred embodiment, the shredded radish is prepared by cutting the radish into 20 cm to 30 cm shreds and drying them at 55° C. to 65° C. for 30 min to 45 min.
[0012] As a preferred embodiment, the soluble Co 2+ The salt is Co(NO3)2·6H2O, CoCl2·H2O, CoCl2·6H2O or (CH3COO)2Co·4H2O.
[0013] As a preferred embodiment, the nitrogen source is CO(NH2)2 or NH4NO3.
[0014] As a preferred embodiment, the freeze-drying is specifically: freezing at -45°C to 40°C for 2 hours, and drying at 4Pa to 5Pa vacuum, 50°C to 60°C for 7 to 8 hours.
[0015] The second object of the present invention is to provide a cobalt nanoparticle / nitrogen-carbon composite material obtained by the above preparation method.
[0016] The third object of the present invention is to provide an application of the above-mentioned cobalt nanoparticle / nitrogen-carbon composite material in the photocatalytic degradation of organic pollutants, wherein the organic pollutants include chloroquine phosphate, doxycycline hydrochloride (DH), oxytetracycline (OTC), tetracycline (TC), methyl orange (MO), Congo red (CR) or methylene blue (MB).
[0017] Compared with the prior art, the present invention has the following beneficial effects:
[0018] The preparation method of the cobalt nanoparticle / nitrogen-carbon composite material provided by the present invention is based on the cell template method to convert soluble Co 2+ The salt and nitrogen source are uniformly dispersed into the radish cells, and the precursor of the cobalt / nitrogen-carbon composite material is obtained after freeze drying and grinding; the precursor of the cobalt / nitrogen-carbon composite material is calcined at a high temperature under a protective atmosphere to obtain the Co 2+The cobalt nanoparticles / nitrogen-carbon composites were obtained by converting the nitrogen source and shredded radish into cobalt nanoparticles, and converting the nitrogen source and shredded radish into nitrogen-carbon composites, thereby achieving high dispersibility and controllable particle size of cobalt nanoparticles, effectively increasing the specific surface area and active sites of cobalt nanoparticles. The prepared cobalt nanoparticles / nitrogen-carbon composites not only enhance the light capture performance, but also the photogenerated electrons can activate peroxymonosulfate (PMS) to produce SO4 ·- It can also induce O2 to produce O2 by decomposing organic pollutant molecules ·- ; Secondly, the photogenerated electrons can reduce the high-valence Co 3+ , cyclically activate PMS to achieve continuous and efficient oxidation degradation of organic pollutants in water.
[0019] The cobalt nanoparticle / nitrogen-carbon composite material prepared by the present invention can efficiently activate PMS to generate free radicals for photocatalytic degradation of organic pollutants due to the large specific surface area of ultrafine cobalt nanoparticles and abundant active sites. The adsorption performance of graphite phase N to PMS is increased, which is conducive to the rapid activation of PMS and the generation of free radicals and singlet oxygen. The cobalt nanoparticle / nitrogen-carbon composite material is light and easy to float, which can improve the light capture performance of the material and increase the new channel for photogenerated electrons to activate PMS to generate free radicals. The carbon shell-coated cobalt nanoparticles prepared by the present invention can slow down the rate at which they are etched, thereby achieving continuous and efficient degradation of organic pollutants in water.
[0020] The cobalt nanoparticle / nitrogen-carbon composite material prepared by the invention is easy to recycle after use, has good reuse effect, and is green, economical, and environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 It is a process flow chart of the preparation of the cobalt nanoparticle / nitrogen-carbon composite material of Examples 1 to 4 of the present invention.
[0022] Figure 2 3 is the XRD diagram of the cobalt nanoparticle / nitrogen-carbon composite material (Co / NC composite material) of Example 1 of the present invention.
[0023] Figure 3 1 is an XPS graph of the cobalt nanoparticle / nitrogen-carbon composite material of the present invention, wherein FIG. a is an element distribution graph of the Co / NC composite material; FIG. b is a C1s spectrum of the Co / NC composite material, FIG. c is a Co 2p spectrum of the Co / NC composite material, FIG. d is a N1s spectrum of the Co / NC composite material, and FIG. e is an O1s spectrum of the Co / NC composite material.
[0024] Figure 4 The diagrams are structural characterization diagrams of the cobalt nanoparticle / nitrogen-carbon composite material of the present invention, wherein diagram a is a scanning electron microscope diagram, diagram b is a transmission electron microscope diagram, diagram c is a high-resolution transmission electron microscope diagram, and diagrams d to g are X-ray spectrometer diagrams.
[0025] Figure 5 The graphs are nitrogen adsorption-desorption curves and pore size distribution curves of the cobalt nanoparticle / nitrogen-carbon composite material of the present invention, wherein graph a is a nitrogen adsorption-desorption curve, and graph b is a pore size distribution curve.
[0026] Figure 6 The graph is a photocatalytic degradation curve of chloroquine phosphate by the cobalt nanoparticle / nitrogen-carbon composite material of the present invention.
[0027] Figure 7 The figure is a diagram showing the degradation effect of the cobalt nanoparticle / nitrogen-carbon composite material of the present invention on chloroquine phosphate and common antibiotic and dye pollutants in different water qualities.
[0028] Figure 8 This is a graph showing the degradation efficiency of chloroquine phosphate by cyclic photocatalytic degradation of the cobalt nanoparticle / nitrogen-carbon composite material of the present invention. DETAILED DESCRIPTION
[0029] In order to enable those skilled in the art to better understand the technical solution of the present invention and implement it, the present invention is further described below in conjunction with specific examples, but the examples are not intended to limit the present invention. The following test methods and detection methods, unless otherwise specified, are conventional methods; the reagents and raw materials, unless otherwise specified, are commercially available.
[0030] The background technology of the present invention mentions: First, the existing pure carbon photocatalytic degradation materials have low catalytic degradation efficiency for organic matter. Second, since ultrafine cobalt nanoparticles are easy to agglomerate and the particle size is difficult to control, the catalytic performance of organic pollutant degradation materials prepared using them as raw materials is unstable. Based on the above technical problems, the present invention provides a preparation method and application of cobalt nanoparticle / nitrogen-carbon composite materials.
[0031] The technical solution of the present invention is analyzed and explained in detail below.
[0032] The present invention first provides a method for preparing a cobalt nanoparticle / nitrogen-carbon composite material, comprising the following steps:
[0033] Soak the shredded radish in a 35℃~45℃ water containing soluble Co 2+ Salt and nitrogen source solution, based on the cell template method, soluble Co 2+ The salt and nitrogen source are evenly dispersed into the radish cells, and after freeze drying and grinding, the precursor of the cobalt / nitrogen-carbon composite material is obtained;
[0034] The precursor of the cobalt / nitrogen-carbon composite material is heated to 400° C. to 450° C. under a protective atmosphere and calcined to obtain the Co 2+The nitrogen source and shredded radish are converted into nitrogen-carbon to obtain a cobalt nanoparticle / nitrogen-carbon composite material.
[0035] In the above technical scheme, radish is used as raw material to prepare Co / NC composite material based on cell template method. Since plant cells are naturally isolated nanocavities and have a strong ability to absorb inorganic salts, soluble Co 2+ The salt and nitrogen source are evenly dispersed in the radish cells to prepare ultrafine cobalt nanoparticles, avoiding the aggregation of cobalt nanoparticles and achieving controllable particle size. After high-temperature anaerobic calcination, not only nitrogen-carbon is generated, but also ultrafine cobalt nanoparticles are dispersed in the nanoshell of nitrogen-carbon, thus solving the problem of uncontrollable particle size of cobalt nanoparticles. Through the combination of nitrogen-carbon and cobalt nanoparticles, the number of recycling of cobalt nanoparticles / nitrogen-carbon composite materials is increased.
[0036] In order to improve the photocatalytic degradation performance of the cobalt nanoparticle / nitrogen-carbon composite material for organic pollutant degradation, the cobalt nanoparticle loading amount of the cobalt nanoparticle / nitrogen-carbon composite material is 3% to 5%, and the nitrogen atomic fraction is 1.9% to 2.2%.
[0037] In order to further increase the loading amount of cobalt nanoparticles and the ratio of nitrogen-carbon, the immersion time is 10 to 12 hours.
[0038] In order to increase the loading amount of cobalt nanoparticles, the shredded radish is prepared by cutting the radish into 20-30 cm shreds and drying them at 55-65° C. for 30-45 minutes.
[0039] It should be noted that the soluble Co used in the present invention 2+ The salt is Co(NO3)2·6H2O, CoCl2·6H2O or (CH3COO)2Co·4H2O, and the nitrogen source used is CO(NH2)2 or NH4NO3. In the preparation process, Co(NO3)2·6H2O provides both the cobalt source and the nitrogen source. When CoCl2·H2O or CoCl2·6H2O is used to provide Co 2+ When NH4NO3 is used as nitrogen source; when (CH3COO)2Co·4H2O is used to provide Co 2+ When using CO(NH2)2 or NH4NO3 as nitrogen source.
[0040] It should be noted that the freeze drying specifically includes: freezing at -45°C to 40°C for 2 hours, and drying at 4Pa to 5Pa vacuum and 50°C to 60°C for 7 to 8 hours.
[0041] The Co / NC composite material prepared as above was applied to the photocatalytic degradation of organic pollutants, achieving efficient degradation of various organic pollutants, including chloroquine phosphate, doxycycline hydrochloride (DH), oxytetracycline (OTC), tetracycline (TC), methyl orange (MO), Congo red (CR) or methylene blue (MB).
[0042] The technical effects of the present invention are described in detail below through specific embodiments and comparative examples.
[0043] Green radish was used as raw material (Ling Yu, bred by the College of Horticulture, Northwest Agriculture and Forestry University), and cobalt nitrate provided both cobalt and nitrogen sources, and cobalt nanoparticles / nitrogen-carbon composites, namely HU-Co / NC composites, were prepared based on the cell template method. Plant cells are naturally isolated nanocavities. Plant cells have a strong ability to absorb inorganic salts. Cobalt nitrate is evenly dispersed in radish cells to prepare ultrafine cobalt nanoparticles, which avoids the aggregation of cobalt nanoparticles and achieves controllable particle size. At the same time, cobalt nitrate provides a nitrogen source, and after high-temperature anaerobic pyrolysis, ultrafine cobalt nanoparticles are dispersed in nitrogen-carbon nanoshells, thereby solving the problem of uncontrollable particle size of cobalt nanoparticles. It can also increase the number of recycling times of the catalyst through the combination of nitrogen-carbon and cobalt nanoparticles.
[0044] Example 1
[0045] A method for preparing a cobalt nanoparticle / nitrogen-carbon composite material comprises the following steps:
[0046] S1, preparation of cobalt / nitrogen-carbon composite material precursor: peel naturally grown mature green radish, cut into 20 cm long threads, take 20 g and dry at 55 ° C for 30 min, add 70 mmol cobalt nitrate, add 50 mL water and stir to dissolve evenly, soak under 35 ° C hydrothermal conditions for 10 h, after preliminary dehydration treatment, freeze-dry, grind into powder, and obtain a cobalt / nitrogen-carbon composite material precursor, recorded as Co / NC precursor.
[0047] S2, placing the precursor in a tube furnace and calcining it at 400° C. in a nitrogen atmosphere for 2 h to obtain a cobalt nanoparticle / nitrogen-doped carbon composite material, which is denoted as Co / NC composite material.
[0048] Example 2
[0049] A method for preparing a cobalt nanoparticle / nitrogen-carbon composite material comprises the following steps:
[0050] S1, preparation of cobalt / nitrogen-carbon composite material precursor: peel naturally grown mature radish, cut into 30 cm long threads, take 40 g and dry at 65 ° C for 45 min, add 80 mmol cobalt nitrate, add 80 mL water and stir to dissolve evenly, soak under 45 ° C hydrothermal conditions for 12 h, after preliminary dehydration treatment, freeze-drying, grind into powder, and obtain a cobalt / nitrogen-carbon composite material precursor, recorded as Co / NC precursor.
[0051] S2, placing the precursor in a tube furnace and calcining it at 450° C. in a nitrogen atmosphere for 2 h to obtain a cobalt nanoparticle / nitrogen-doped carbon composite material, which is denoted as Co / NC composite material.
[0052] Example 3
[0053] A method for preparing a cobalt nanoparticle / nitrogen-carbon composite material comprises the following steps:
[0054] S1, preparation of cobalt nanoparticle / nitrogen-carbon composite material precursor: peel and cut naturally grown mature green radish into 20 cm to 30 cm filaments, take 50 g and dry it at 60°C for 40 min, add 100 mmol cobalt nitrate, add 100 mL water and stir to dissolve evenly, soak it under hydrothermal conditions at 40°C for 10 h, freeze-dry it after preliminary dehydration, grind it into powder, and obtain a cobalt / nitrogen-carbon composite material precursor, recorded as Co / NC precursor.
[0055] S2, placing the precursor in a tube furnace and calcining at 420° C. for 2 h to obtain a cobalt nanoparticle / nitrogen-carbon composite material, denoted as Co / NC composite material.
[0056] Example 4
[0057] A method for preparing a cobalt nanoparticle / nitrogen-carbon composite material comprises the following steps:
[0058] S1, preparation of cobalt / nitrogen-carbon composite material precursor: peel naturally grown mature radish, cut into 20 cm to 30 cm wire, take 70 g and dry it at 62 ° C for 40 min, add 140 mmol cobalt nitrate, add 140 mL water and stir to dissolve evenly, soak under 38 ° C hydrothermal conditions for 11 h, after preliminary dehydration treatment, freeze-drying, grind into powder, and obtain a cobalt / nitrogen-carbon composite material precursor, recorded as Co / NC precursor.
[0059] S2, placing the precursor in a tube furnace and calcining at 420° C. for 2 h to obtain a cobalt nanoparticle / nitrogen-carbon composite material, denoted as Co / NC composite material.
[0060] In order to further illustrate the technical effect of the present invention, the present invention also sets a comparative example, which is as follows:
[0061] Comparative Example 1
[0062] Compared with Example 1, the difference is that cobalt nitrate is adjusted to cobalt chloride.
[0063] A method for preparing a cobalt nanoparticle / biochar composite material comprises the following steps:
[0064] S1, preparation of the precursor of cobalt nanoparticle / biochar composite material: peel the naturally grown mature green radish, cut it into 20 cm long threads, take 20 g and dry it at 55°C for 30 min, add 70 mmol of cobalt chloride, add 50 mL of water and stir to dissolve evenly, soak it under hydrothermal conditions at 35°C for 10 h, freeze-dry it after preliminary dehydration treatment, grind it into powder, and obtain a cobalt / carbon composite material precursor, recorded as Co / C precursor.
[0065] S2, placing the precursor in a tube furnace and calcining it at 400 °C in a nitrogen atmosphere for 2 h to obtain a cobalt nanoparticle / biochar composite material, which is denoted as Co / C composite material.
[0066] Comparative Example 2
[0067] Compared with Example 1, the difference is that only cobalt nanoparticles are prepared.
[0068] A method for preparing cobalt nanoparticles comprises the following steps:
[0069] 70 mmol of cobalt nitrate was placed in a tube furnace and calcined at 400° C. in a nitrogen atmosphere for 2 h to obtain cobalt nanoparticles, which were recorded as Co nanoparticles.
[0070] The morphology and properties of the cobalt nanoparticle / nitrogen-carbon composite material prepared in the above example were characterized, and the results are shown below.
[0071] Figure 1 The present invention is a process flow chart for preparing the cobalt nanoparticle / nitrogen-carbon composite material. The material preparation is divided into 4 steps: the first step: washing the green radish for use; the second step: shredding; the third step: soaking; the fourth step: high-temperature pyrolysis under nitrogen protection.
[0072] Figure 2 This is the XRD pattern of the cobalt nanoparticle / nitrogen-carbon composite material prepared in Example 1 of the present invention. Figure 2 It can be seen that the characteristic peaks of Co nanoparticles appear at 44°, 51°, and 75°, respectively, indicating that cobalt nanoparticles are successfully loaded on the composite material.
[0073] Figure 3 This is the XPS graph of the Co / NC composite material prepared in Example 1 of the present invention. Figure 3 As shown in Figure 2, the elemental composition and valence state of Co / NC composites were analyzed using XPS. Figure 3As shown in Figure a, the main elements in Co / NC composite materials are C, Co, N and O. Figure 3 Figure b is a high-resolution C1s spectrum of the Co / NC composite material, in which there are three characteristic peaks at 284.8eV, 286.1eV and 289.1eV, corresponding to CC, C=N and C=O bonds respectively; Figure 3 As shown in the high-resolution Co 2p spectrum of Figure c, there are two characteristic peaks at 781.3eV and 797.3eV, corresponding to Co 2p 3 / 2 and Co 2p 1 / 2 orbit, and is accompanied by the appearance of satellite peaks; Figure 3 As shown in the high-resolution N1s spectrum of Figure d, there are three characteristic peaks at 398.3eV, 399.0eV and 400.0eV, corresponding to the characteristic peaks of graphite-N, pyridine-N and pyrrole-N, respectively, proving that three different structures of nitrogen-carbon are produced in the Co / NC composite material; Figure 3 As shown in the high-resolution O1s spectrum of Figure e, there are two characteristic peaks at 531.4eV and 532.7eV, corresponding to the characteristic peaks of adsorbed oxygen and molecular oxygen, respectively. The XPS results confirmed the successful synthesis of the Co / NC composite material.
[0074] Figure 4 The scanning electron microscope image, transmission electron microscope image, high-resolution transmission electron microscope image and X-ray energy spectrum image of the Co / NC composite material prepared in Example 1 show that a large number of ultrafine cobalt nanoparticles exist on the surface of the Co / NC composite material; the transmission electron microscope image shows that the particle size statistics of the ultrafine cobalt nanoparticles on the surface of the Co / NC composite material in the area in the figure are carried out, and the particle size of the nanoparticles is between 1nm and 10nm, showing a normal distribution, and the average particle size is 5.635±1.693nm; the high-resolution transmission electron microscope image of the Co / NC composite material shows that the ultrafine nano cobalt ions loaded on the surface of the Co / NC composite material have a smooth solid texture, and the (111) lattice fringes of Co can be seen, and the lattice spacing of the Co single crystal is 0.203nm; Co, N, and O elements are evenly distributed on the surface of the nitrogen-carbon material.
[0075] Figure 5 The nitrogen adsorption-desorption curve (a) and pore size distribution curve (b) of the cobalt nanoparticle / nitrogen-doped carbon composite material are shown in Figure 1. The pore size distribution is mainly concentrated in the range of 4 to 5 nm. The specific surface area of the composite material is 4.34 m 2 / g.
[0076] The photocatalytic degradation performance of the Co / NC composite material prepared in Example 1 of the present invention on chloroquine phosphate and various organic pollutants was tested, and the results are as follows.
[0077] 20 mg of cobalt nanoparticles / nitrogen-carbon composite material was placed in a beaker, and 50 mL of 50 mg / L chloroquine phosphate aqueous solution was added. Static adsorption was carried out for 20 min in the dark at 298 K and pH = 6. Then 2 mmol of PMS was added and reacted for 10 min under 300 W xenon lamp irradiation.
[0078] Figure 6 is the photocatalytic degradation curve of chloroquine phosphate by cobalt nanoparticles / nitrogen-carbon composites. Figure 6 It can be seen that the photocatalytic degradation efficiency of Co / NC composite material for chloroquine phosphate can reach 99.9%, and the degradation is basically completed in 6 minutes. Pure Co nanoparticles have almost no degradation performance on chloroquine phosphate. The photocatalytic degradation of chloroquine phosphate by Co / C composite material is 24.6%. Obviously, Co / NC has the synergy of ultrafine Co nanoparticles and nitrogen-carbon.
[0079] Figure 7 The degradation performance of cobalt nanoparticles / nitrogen-carbon composite materials on chloroquine phosphate and common antibiotics and dyes in different water qualities. According to the different water qualities, four different water qualities, deionized water, tap water, reservoir water and river water, were selected to degrade chloroquine phosphate, doxycycline hydrochloride, oxytetracycline, tetracycline, methyl orange, Congo red and methylene blue, and the degradation efficiency was more than 99%.
[0080] Figure 8 The cyclic photocatalytic degradation of chloroquine phosphate by cobalt nanoparticles / nitrogen-carbon composites was demonstrated. After 6 cycles of photocatalytic degradation, the degradation efficiency of chloroquine phosphate by the Co / NC composite was still higher than 92%.
[0081] In summary, the present invention achieves high dispersibility and controllable particle size of cobalt nanoparticles, effectively increases the specific surface area and active sites of cobalt nanoparticles, and efficiently activates PMS to generate free radicals for photocatalytic degradation of organic pollutants. The cobalt nanoparticle / nitrogen-carbon composite material (Co / NC) of the present invention is light and easy to float, improves the light capture performance of the composite material, increases new channels for photogenerated electrons to activate PMS to generate free radicals, and achieves efficient degradation of organic pollutants in water.
[0082] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A method for preparing a cobalt nanoparticle / nitrogen-carbon composite material, characterized in that: The following steps are involved: Soak the shredded radish in a 35℃~45℃ water containing soluble Co 2+ Salt and nitrogen source solution, based on the cell template method, soluble Co 2+ The salt and nitrogen source are evenly dispersed into the radish cells, and after freeze drying and grinding, the precursor of the cobalt / nitrogen-carbon composite material is obtained; The precursor of the cobalt / nitrogen-carbon composite material is heated to 400° C. to 450° C. under a protective atmosphere and calcined to obtain the Co 2+ The nitrogen source and shredded radish are converted into nitrogen-carbon to obtain a cobalt nanoparticle / nitrogen-carbon composite material.
2. The preparation method according to claim 1, characterized in that: In the cobalt nanoparticle / nitrogen-carbon composite material, the loading amount of the cobalt nanoparticles is 3% to 5%, and the nitrogen atomic fraction is 1.9% to 2.2%.
3. The preparation method according to claim 1, characterized in that: The soaking time is 10 to 12 hours.
4. The preparation method according to claim 1, characterized in that: The calcination time is 2h.
5. The preparation method according to claim 1, characterized in that: The shredded radish is prepared by cutting the radish into 20-30 cm shreds and drying them at 55-65° C. for 30-45 minutes.
6. The preparation method according to claim 1, characterized in that: The soluble Co 2+ The salt is Co(NO3)2·6H2O, CoCl2·H2O, CoCl2·6H2O or (CH3COO)2Co·4H2O.
7. The preparation method according to claim 1, characterized in that: The nitrogen source is CO(NH2)2 or NH4NO3.
8. The preparation method according to claim 1, characterized in that: The freeze drying specifically includes: freezing at -45°C to 40°C for 2 hours, and drying at 4Pa to 5Pa vacuum and 50°C to 60°C for 7 to 8 hours.
9. A cobalt nanoparticle / nitrogen-carbon composite material prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the cobalt nanoparticle / nitrogen-carbon composite material according to claim 9 in photocatalytic degradation of organic pollutants, characterized in that: The organic pollutants include chloroquine phosphate, doxycycline hydrochloride, oxytetracycline, tetracycline, methyl orange, Congo red or methylene blue.
Citation Information
Cited By
Hollow nitrogen-doped carbon-loaded Zn-Co catalyst, preparation method and application
CN119746902A
A hollow nitrogen-doped carbon-supported Zn-Co catalyst, preparation method and application
CN119746902B